Ionic Liquid Additives in Water-Based Lubricants for Bearing Steel – Effect of Electrical Conductivity and pH on Surface Chemistry, Friction and Wear - Wijanarko, W.; Khanmohammadi, H.; Espallargas, N. (Frontiers in Mechanical Engineering, 2022)
Water-based lubricants have the potential to become the largest environmentally friendly lubricants in applications such as electric vehicles and the newly emerging green technologies of the future due to their inherent low viscosity and cooling properties. In order to be environmentally acceptable (EAL), both base lubricants and additives should comply with biodegradability, non-toxicity, and non-bioaccumulation requirements. Additives for water-based lubricants should ideally be polar and soluble in water and, at the same time, should not increase the electrical conductivity to critical levels for corrosion. However, most additives used in synthetic or mineral oils are non-polar. Ionic liquids have recently gained attention as lubricant additives due to their high polarity, making them highly surface-active (i.e. high tendency to adsorb on metal surfaces). However, they are seen as highly corrosive for many metal alloys. In this work, a water-glycol lubricant containing two different ionic liquids has been investigated as a potential green lubricant for a bearing steel AISI 52100 with accurate control on electrical conductivity and pH. The selected ionic liquids were tributylmethylphosphonium dimethylphosphate (PP) and 1-butyl-1-methylpyrrolidinium tris(pentafluoroethyl)trifluorophosphate (BMP). The tribological behaviour of the ionic liquids was compared with a well-known organic friction modifier, dodecanoic acid (C12). The ionic liquids showed lower friction and wear rate than the water-based lubricant alone. However, they showed higher friction than the lubricant formulated with C12, in which PP gave lower friction than BMP due to low pH. A detailed subsurface analysis of the wear track using scanning-transmission electron microscopy (STEM) showed that a thick oxide tribofilm was built on the wear track for both lubricants formulated with ionic liquids due to high electrical conductivity. This tribofilm gave beneficial effect on wear. Although PP and BMP gave thicker tribofilms than C12, it was not durable, resulting in cracking and detachment.